Foundation of the Third Renaissance (Eurasian Research Bulletin, 2023)
Ravshanbek Kasim ugli, a talented poet who lives in Shahrikhan district, author of apologues on current issues of our time, is such a representative of our nation. Teacher's family goes back to Burkhaniddin Eshon (Eshon- owner of dedication) who was one of the Sayids. This article are about this poet.